Matrix remodelling enzymes, the protease cascade and glycosylation. - Van den Steen, P; Opdenakker, G; Wormald, M; Dwek, R; Rudd, P (2001)
Glycosylation influences the specific activities of serine proteases including tissue-type plasminogen activator and plasmin which act together in a ternary complex with fibrin. Serine proteases and matrix metalloproteinases (MMPs), including gelatinase B, participate in a protease cascade to remodel the extracellular matrix. In addition to the recognition and targeting functions of carbohydrates and the fact that they confer protease resistance on glycoproteins, oligosaccharides may extend particular protein domains of matrix remodelling enzymes and fine-control their activities within the context of the extracellular matrix. For example, the sialic acids of gelatinase B influence the catalytic activity of this enzyme in a complex with the tissue inhibitor of metalloproteinases-1 (TIMP-1).